Autonomic Nervous System - Svorc, Pavol (IntechOpen, 2018)
The autonomic nervous system is one of the most important involuntary control mechanisms that primarily controls and modulates the functions of the visceral organs. The book discusses some of the specificities of the autonomic nervous system in terms of dendritic development in the sympathetic compartment, as well as a detailed description of noradrenergic groups and their key role in the modulation of all antinociceptive and autonomic responses elicited by painful or threatening situations. In the book, only those cases are mentioned that are closely related to disorders or changes of function of the autonomic nervous system. This book can evoke interest in many researchers who want to use the information for the advancement of their research towards a better understanding of the autonomic regulatory mechanisms.